Subacute combined degeneration associated with vitamin E deficiency due to small bowel obstruction: A case report. Issue 36 (September 2019) - Jung, Jong Burm; Kim, Yuntae; Oh, Kiyoung; Kim, Soo A; Doh, Joung Hyun; Oh, Hye Jeong; Seok, Jin Myoung
Abstract: Rationale: There have been a few reported cases of subacute combined degeneration (SCD) associated with vitamin E deficiency, but the period of intestinal malabsorption was more than several years. We present a rare case of acute onset SCD that occurred in a relatively short period of several weeks with vitamin E deficiency related to small bowel obstruction. Patient concerns: A 50-year-old woman had abdominal pain. A small bowel obstruction was suspected and conservative treatment was performed. She underwent bowel surgery after 2 weeks without any improvement. Following the operation, she was in a state of reduced consciousness. She was treated in an intensive care unit. Her consciousness level gradually recovered to alert in a week, but other symptoms such as ataxia, weakness on limbs, severe dysarthria, and dysphagia occurred. Since then, she had spent nearly 6 weeks in a bed-ridden state without improving. Diagnosis: SCD associated with vitamin E deficiency was confirmed by laboratory investigations, electrophysiologic test, and whole spine magnetic resonance imaging scans. Interventions: For vitamin E supplementation, she was administered a dose of 1200 mg/d. Physical therapy was focused on strengthening exercise, balance, and walker gait training. Occupational therapy was focused on activities of daily living training and dysphagia rehabilitation. Outcomes: After 6 weeks, her muscle strengths and functional level were substantially improved. The vitamin E level was recovered to normal range. Lessons: This case suggests that if neurological symptoms occur in patients with intestinal obstruction, clinicians need to consider a deficiency of micronutrients such as vitamin E and vitamin B12. Patients with short clinical courses suffer less neurological damage and achieve faster recovery.